1996
DOI: 10.3181/00379727-211-43951
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of Resistance to Thyroid Hormone: Insights into Thyroid Hormone Action

Abstract: Thyroid hormones (T3, T4) exert multiple cellular effects through nuclear thyroid hormone receptors (TR alpha, TR beta). Thyroid hormone receptors are transcription factors that act by altering patterns of gene expression. Resistance to thyroid hormone (RTH) is a rare disorder caused by mutations in the TR beta gene. Biochemically, the syndrome is defined by elevated circulating levels of free thyroid hormones due to reduced target tissue responsiveness and normal, or elevated, levels of thyroid-stimulating ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 64 publications
0
42
0
1
Order By: Relevance
“…RTH-Syndrome TR mutants exhibit dominant-negative properties virtually identical to those described here for the HCC TR mutants, are expressed in a wide range of tissues, including hepatocytes, yet RTH Syndrome is not known to increase the incidence of HCC (Refetoff, 1993;DeGroot, 1996;Kopp et al, 1996;Chaterjee, 1997;. Notably, RTH-Syndrome mutations are characteristically single substitutions that map to the hormone-binding domain, whereas many of the HCC mutants have sustained multiple substitutions that encompass lesions in the DNA recognition domain of the receptor (Refetoff, 1993;DeGroot, 1996;Kopp et al, 1996;Chaterjee, 1997;Lin et al, 1999).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…RTH-Syndrome TR mutants exhibit dominant-negative properties virtually identical to those described here for the HCC TR mutants, are expressed in a wide range of tissues, including hepatocytes, yet RTH Syndrome is not known to increase the incidence of HCC (Refetoff, 1993;DeGroot, 1996;Kopp et al, 1996;Chaterjee, 1997;. Notably, RTH-Syndrome mutations are characteristically single substitutions that map to the hormone-binding domain, whereas many of the HCC mutants have sustained multiple substitutions that encompass lesions in the DNA recognition domain of the receptor (Refetoff, 1993;DeGroot, 1996;Kopp et al, 1996;Chaterjee, 1997;Lin et al, 1999).…”
Section: Discussionmentioning
confidence: 80%
“…Notably, RTH-Syndrome mutations are characteristically single substitutions that map to the hormone-binding domain, whereas many of the HCC mutants have sustained multiple substitutions that encompass lesions in the DNA recognition domain of the receptor (Refetoff, 1993;DeGroot, 1996;Kopp et al, 1996;Chaterjee, 1997;Lin et al, 1999). This suggests the possibility that the altered disease proclivities of these HCC TR mutants might be because of an alteration in their DNA sequence recognition specificity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This may be explained by individual differences in the distribution of TRa and TRb in the tissues (2,3,26). Moreover, variations in expression of the mutant TRb and the extent to which it inhibits the wild-type TRb (4,27) or other nuclear receptors (28) may contribute to this diversity. Our study demonstrated no significant difference in FT4 and T4 levels between unaffected family members and unrelated spouse controls.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is associated with diverse mutations in the thyroid hormone receptor b (hTRb) gene which encodes a ligand-dependent nuclear transcription factor that modulates the transcription of target genes by interacting with thyroid response elements (TREs) in their promoter region (3)(4)(5)(6). The TRb gene undergoes alternate splicing to generate two receptor isoforms, TRb1 and TRb2, the latter differing from b1 in the N-terminus and being mainly expressed in the pituitary (7).…”
Section: Introductionmentioning
confidence: 99%